2017
DOI: 10.2147/ijn.s123484
|View full text |Cite
|
Sign up to set email alerts
|

Stromelysin-2 (MMP-10) facilitates clearance and moderates inflammation and cell death following lung exposure to long multiwalled carbon nanotubes

Abstract: Multiwalled carbon nanotubes (MWCNTs) are nanomaterials composed of multiple layers of graphene cylinders with unique properties that make them valuable for a number of industries. However, rising global production has led to concerns regarding potential occupational exposures to them as raw materials during handling. This is especially true for long MWCNT fibers, whose aspect ratio has been posited to initiate pathology similar to that of asbestos. Matrix metalloproteinases (MMPs) are a class of extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In the inflammatory setting triggered by acute infection, MMP-10 produced by macrophages moderates inflammation and protects against tissue damage (41,48,49). Similar protective effects are seen in lung injury caused by inhalation of long multiwalled carbon nanotubes (50). Studies of MMP-9 in lung disease have shown context-dependent profibrotic and anti-fibrotic effects in different models of lung fibrosis (51).…”
Section: Discussionmentioning
confidence: 92%
“…In the inflammatory setting triggered by acute infection, MMP-10 produced by macrophages moderates inflammation and protects against tissue damage (41,48,49). Similar protective effects are seen in lung injury caused by inhalation of long multiwalled carbon nanotubes (50). Studies of MMP-9 in lung disease have shown context-dependent profibrotic and anti-fibrotic effects in different models of lung fibrosis (51).…”
Section: Discussionmentioning
confidence: 92%
“…MMP-10 is a secreted metalloproteinase with a key role on modulation of macrophage activation and function. MMP-10 is not expressed in unchallenged tissues, but is increased in response to a variety of insults [44]. Thus, a positive correlation of MMP-10 CSF levels with disease progression might indicate increased inflammation and neuronal loss.…”
Section: Discussionmentioning
confidence: 99%
“…MMP10 participates in many physiological and pathological processes, and plays an important role in embryonic development, tissue damage repair and other processes [26]. Recent research shows that MMP10 plays a signi cantly important role in the activation of pro MMPs [27]; MMP10 is highly expressed in epithelial tumors such as gastric cancer, bladder transitional cell cancer, esophageal cancer, skin cancer and non-small cell lung cancer [17,[28][29][30]. In our study, we found that knockdown MMP10 in A549 cells by MMP10 siRNA could signi cantly inhibit the proliferation and promoted apoptosis after IR.…”
Section: Discussionmentioning
confidence: 99%